THE EFFCCTS OF PHENOMENON - BASED LEARNING PROVISION ON HEALTH LITERACY FOR YOUNG CHILDREN: ผลการจัดการเรียนรู้โดยใช้ปรากฏการณ์เป็นฐานที่มีต่อความฉลาดรู้ทางสุขภาวะสำหรับเด็กปฐมวัย - Buaphan, Natethip; Samahito, Chalatip; Lehmongkol, Pattamavadi (Journal of Education and Innovation, 2023)
The purpose of this study was to study the effects of phenomenon-based learning provision on health literacy of young children. Health literacy of young children in 6th sides including access skill, cognitive skill, communication skill, self-management skill, decision skill, and media literacy skill. The samples of this study were 25 preschool children who were studying in Kindergarten. Received of phenomenon-based learning it took 10 weeks to collect the data. The research instruments were consisted phenomenon-based learning lesson plans which is adapted from the concept of Daehler and Folsom (2016), early childhood health literacy evaluation form and notes after the phenomenon-based learning activity provision was over. Data was analyzed by means, standard deviation, t-test (dependent) and content analysis. The results of the study showed that the children who received phenomenon-based learning provision had higher post-test health literacy scores than the pre-test. In addition, statistically significant at the level .05, the children had increased health literacy, including the skills of access, cognitive, communication, self – management, decision making, and media literacy.